MERETAS NILAI EKONOMI MANAJEMEN - Imahda Khoiri Furqon (Adzkiya : Jurnal Hukum dan Ekonomi Syariah, 2019)
The purpose of this study is to obtain information on the management of entrepreneurial leadership competency, the obstacles in the management of entrepreneurial leadership, and solutions to overcome barriers of entrepreneurial leadership management of the leader at Sanggung, Gatak, Sukoharjo in 2016. This research approach used qualitative research. This research was conducted at Sanggung village in April until June 2016. Subject of this research was the leader of Sanggung village, while the informants were Secretary, Head of Government Affairs, Head of Public Welfare Affairs, BPD, Public Figure, and BKM. Technique of collecting data used interviews, observation and documentation. Data analysis used an interactive model.The results of the research are: 1) the leader of Sanggung in conducting leadership management of entrepreneurship competency is shown by village building program of entrepreneurship-oriented. This program is described in short-term and middle-term planning. Leadership management of entrepreneurial competency has the following stages: planning of work program, organizing, implementing, facilitating, and monitoring of evaluation. 2) there are several obstacles in the leader of Sanggung in conducting leadership management of entrepreneurship competencyincluding: a) lack of expert, b) limited entrepreneurship education and training for the community, the budget for the implementation of education and training for entrepreneurship is also very minimal; c) generally, the society depends on working capital, entrepreneurship defined by the amount of working capital is not the spirit to work to face the challenges in producing products according to market needs. 3) There are three solutions that have been programmed by the leader, there are: a) cooperation with entrepreneurial experts so that the logical consequence is reachable. Recently, the regional government represented by the leader is approaching to bridge cooperation with entrepreneurial expert; b) mapping instructor in accordance with the priorities of education and training materials; c) continuous motivation given to the public to do the entrepreneurial spirit, to get ready to face the challenge, and to meet the needs of the market.